Current trends in the treatment of complications in patients with gastric and duodenal ulcer disease (review of foreign literature) - V. I. Belokonev; S. Yu. Pushkin; K. P. Yadav; A. A. Serov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Peptic ulcer disease is a common disease that occurs in 5–10 % of the world population. Despite the sharp decrease in morbidity and hospitalization rates of patients with peptic ulcer disease of the stomach and duodenum, for the last 30 years lethality in such patients remains at a high level, and complications occur with a frequency of 10–20 %. Purpose: to present the literature review of foreign researchers devoted to the modern trends of complications treatment in patients with peptic ulcer and duodenal ulcer disease. Material and methods. Literature sources in English on this topic in PubMed, MEDUNE, Google Scholar databases were analyzed. The review highlights clinical studies devoted to the treatment of complications of gastric and duodenal ulcer disease: ulcer bleeding, perforative ulcer, and pyloroduodenal stenosis. Conclusion. Complications of gastric and duodenal ulcer disease remain complex therapeutic and surgical problems. Despite the achieved successes, the results of treatment of complications remain unsatisfactory, which requires further study and search for their improvement.